Advanced thermally assisted surface engineering processes - Chattopadhyay, Ramnarayan (Boston : Kluwer Academic, 2004)
"Advanced Thermally Assisted Surface Engineering Processes has been structured to provide assistance and guidance to the engineers, researchers and students in choosing the right process from the galaxy of newer surface engineering techniques using advanced heat sources."--BOOK JACKET.
Ch. 1. Wear, Surface, Heat and Surface Engineering -- Ch. 2. Plasma Assisted Thermal Processes -- Ch. 3. Ion Beam Processes -- Ch. 4. Electron Beam Processes -- Ch. 5. Microwave Assisted Surface Modification Processes -- Ch. 6. Laser Assisted Surface Engineering Processes -- Ch. 7. Solar Energy for Surface Modifications -- Ch. 8. Combustion Processes for Surface Modification -- Ch. 9. Friction Weld Surfacing -- Ch. 10. Induction Surface Modification Processes -- Ch. 11. Surfacing by Spark Deposition Processes -- Ch. 12. Arc Assisted Advanced Surface Engineering Processes -- Ch. 13. Hot Isostatic Press -- Ch. 14. Fluid Bed Processes -- Ch. 15. Polymeric Surfaces -- Ch. 16. Ceramic Surfaces -- Ch. 17. Diffused and CVD Coatings of Single and Multiple Elements -- Ch. 18. Miscellaneous Processes -- Ch. 19. Quality of the Engineered Surfaces -- Ch. 20. Prognostic and Life Cycle Extension.
0
Includes bibliographical references and index.
Keywords: Surfaces (Technology)